Pengaruh Asimetri Informasi Terhadap Kebijakan Dividen Pada Perusahaan Pertambangan Sub Sektor Batu Bara di Bursa Efek Indonesia - Trifika Anggun Sari; Muhamad Helmi (P3M STIE Mulia Darma Pratama, 2019)
Managers who know internal information and company prospects sometimes do not convey to investors transparently. This causes information asymmetry issues that will affect the dividend policy. The problem formulation in this research is how the development and influence of earning forecast error, company size and the opportunity to grow toward dividend policy both partially and simultaneously. This research aims to determine the influence of the asymmetry of the information that is proscribed with earning forecast errors, sizes, and opportunities to grow toward the dividend policy. The research used the Purposive sampling method for sampling, with the criteria: (1) The company including coal sub-sector mining company which was successively registered in ISE during the period 2012-2017, (2) Dividend policy data is available during the estimated period of observation, (3) the company which is in its financial statements has complete data on DPR ratio, earning forecast error, company size and MBVA during the estimated period of observation. There are 5 companies mining companies of coal sub-sector as samples. The analytical techniques used are multiple linear regressions. Based on the results of data analysis, it can be concluded that partially earning forecast error and the chance of growing affects partially and significantlytoward the dividend policy, while the size of the company does not partially affect toward the dividend policy. While simultaneously it was shown that at least one variable X (earning forecast error, company size and opportunity to grow) that affects the dividend policy and Adjusted R Square, the ability to explain variables provided by these three variables is 34.1%.